The Research on Stability of the Russian Banking System by Machine Learning Methods - Bayuk, Oleg A.; Berzin, Dmitry V.; Timov, Bogdan A. (Journal of Reviews on Global Economics, 2018)
The problem of stability of the Russian banking system is investigated. To describe the state of a commercial bank, we use a system of indicators, proposed by F.T. Aleskerov and his colleagues. For predicting the development of banking system, the machine learning system implemented in the Azure ML is used. To optimize the work of this software, it is suggested to use integral indicators.